Genetic diversity of quinoa (Chenopodium quinoa Willd.) germplasm as revealed by sequence-related amplified polymorphism markers - Kularb Laosatit; Siriporn Taytragool; Kotchakon Pimsaythong; Prakit Somta; Orn-u-ma Tanadul (Agriculture and Natural Resources, 2021)
Quinoa (Chenopodium quinoa Willd.) is an excellent example of a functional food being rich in antioxidants and well balanced regarding carbohydrates, lipids and protein, providing an ideal source of essential amino acids for human nutrition. Its nutritional characteristic has been emphasized both in developed and undeveloped regions resulting in many countries growing quinoa as a healthy food. Breeding programs for quinoa in new regions need diverse genetic variety. Therefore, the genetic diversity of 135 quinoa accessions was determined using 21 sequence-related amplified polymorphism (SRAP) markers generated from eight primer pairs. The polymorphic information content (PIC) was in the range 0.10–0.25 with an average of 0.19. Overall genetic diversity was relatively low in the range 0.17–0.40, with a mean of 0.32. Population structure, neighbor-joining tree and principal coordinate analyses revealed that the quinoa accessions were clustered into two groups. One was composed of 85 accessions mainly from the USA and Peru and some accessions from Chile and Bolivia. The other one comprised 50 accessions largely from Bolivia and Chile and some accessions from Peru. The results from this study suggested that the genetic diversity of the quinoa accessions from the USA was relatively low compared with other reports. Therefore, plant breeders need to develop new cultivars by crossing quinoa from different genetic groups or to access additional ex situ germplasm collections.